Faktor - Faktor Yang Mempengaruhi Harga Jual Komoditas Kembang Kol (Brassica oleacera Var. Botrytis ) ( Suatu Kasus Pada Petani Kembang Kol Di Kecamatan Telagasari Kabupaten Karawang) - Isman Sidik; Wahyu Wahyuna; Rudian Rudian; Jojo Jojo (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2023)
Selling price is one of the factors that greatly affects farmers, one of which is the level of income earned by farmers, which in turn will affect the motivation and work productivity of farmers. The aim of this study was to determine the factors which influence the selling price of farmer-level cabbage flowers in Telagasari District, Karawang Regency. Based on this, this study was conducted to determine what factors influence the selling price of cauliflower at farm level. This research was conducted in Telagasari Subdistrict, Karawang Regency, the location of the study was chosen purposively. The scope of this research was limited to the number of production, quality, postharvest handling and marketing distribution costs. The sample size was determined by simple random sampling based on the formula approach put forward by Toto Warsa and grandchildren SA (1979) of 89 people. The analytical model used was multiple linear functions. The results of the analysis of the coefficient of determination (RÂ²) obtained a value of 0.408 which means that the amount of production, quality, postharvest handling, and marketing distribution channels affect the selling price of cauliflower by 40.8%, while the remaining 59.2% is influenced by other factors. The results of the simultaneous analysis (f-test) that the amount of production, quality, postharvest handling, and marketing distribution costs have a significant effect on the selling price of cauliflower at the farmer level in Telagasari District, Karawang Regency. Partial analysis (t-test) states that the quality factor and distribution costs have a significant effect on the selling price of cauliflower at the farm level.